PLC-BASED WAX COATING SYSTEM PLANNING FOR FOOD PACKAGING CARTONS - Taufiq Hidayat; Nidia Lestari; Joko Waluyo; Venditias Yudha; Arif Budi Asih (Universitas Muhammadiyah Semarang, 2023)
Packaging is the spearhead of marketing because it directly deals with consumers. Technological advances in the world of modern manufacturing and trading industries are competing to innovate to create the highest quality packaging. Paraffin wax coating, which is waterproof can provide resistance to packaging and the strength of a product so that protection is guaranteed against light, gas, harmful bacteria. The wax coating process without the use of large amounts of human labor requires a laminating system with a PLC program. Planning of this control system is supported by the selection of components based on the voltage on the PLC and ladder diagram simulation assistance with CX-Designer software. The simulation results of ladder diagram control system runs well and the application of ON OFF control using no NC instructions, temperature control thermostat, solenoid valve to open the valve in the chamber, and the calculation of the number of cartons that have been laminated with counter instructions and as an OFF signal on the motor.